2009
DOI: 10.1105/tpc.109.067751
|View full text |Cite
|
Sign up to set email alerts
|

bearded-earEncodes a MADS Box Transcription Factor Critical for Maize Floral Development  

Abstract: Although many genes that regulate floral development have been identified in Arabidopsis thaliana, relatively few are known in the grasses. In normal maize (Zea mays), each spikelet produces an upper and lower floral meristem, which initiate floral organs in a defined phyllotaxy before being consumed in the production of an ovule. The bearded-ear (bde) mutation affects floral development differently in the upper and lower meristem. The upper floral meristem initiates extra floral organs that are often mosaic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 54 publications
7
104
0
1
Order By: Relevance
“…Furthermore, OsMAS6 is able to form protein complexes with rice B and D proteins in yeast cells [47,48], resembling the complex formation of SEP proteins with A, B and C in Arabidopsis and other eudicot species [9,54]. Moreover, a physical interaction between BDE and ZAG1 (Zea AGAMOUS 1, a C class protein) in maize has also been shown recently [40].…”
Section: Agl6-like Genes Have a Sep-like Role In Flower Patterningmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, OsMAS6 is able to form protein complexes with rice B and D proteins in yeast cells [47,48], resembling the complex formation of SEP proteins with A, B and C in Arabidopsis and other eudicot species [9,54]. Moreover, a physical interaction between BDE and ZAG1 (Zea AGAMOUS 1, a C class protein) in maize has also been shown recently [40].…”
Section: Agl6-like Genes Have a Sep-like Role In Flower Patterningmentioning
confidence: 95%
“…The monocotyledonous species maize has two AGL6-like genes, ZAG3 and ZAG5 [39]. ZAG3 was expressed in both male and female maize inflorescences [40]. Its expression was found in carpels, but not in stamens, and in the sterile floral organs, but not in glumes [39].…”
Section: Agl6-like Genes Are Closely Related To Sep-and Ap1-like Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…In maize (Zea mays) two AGL6-like genes, zag3 and zag5, have been characterized (Mena et al, 1995). zag3 mRNA in situ hybridization showed that it is expressed in both upper and lower floral meristems but not in the lemma and stamens (Thompson et al, 2009). Later in development, zag3 is expressed in developing lodicules, palea, carpels, and the inner integument.…”
Section: Introductionmentioning
confidence: 99%
“…Later in development, zag3 is expressed in developing lodicules, palea, carpels, and the inner integument. Characterization of a zag3 mutant, the only loss-of-function mutant available for an AGL6-like gene, demonstrates a role in floral meristem and organ development (Thompson et al, 2009). No data are available on the specific floral organs where zag5 is expressed.…”
Section: Introductionmentioning
confidence: 99%